(untitled) (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
The article analyzes some key differences between British English and American English in terms of grammar, vocabulary, pronunciation and idioms. On that basis, the article points out some reasons for that difference and shows the fact that English and American English are still one language but are two very different dialects.